Empowering learners of English as an additional language: translanguaging with machine translation. (1st November 2022) - Kelly, Ronan; Hou, Heng
Abstract: The use of machine translation is increasingly prevalent in language education and social communication. This study explored how multilingual pupils who are learning English as an additional language (EAL) use machine translation within their formal education and everyday lives. A translanguaging framework was employed to understand the ways in which learners use machine translation and how they interpret these practices. Qualitative data was collected from a series of pupil (n = 28) focus groups and teacher (n = 14) interviews across five secondary schools in Northern Ireland. The findings demonstrate that machine translation permeates various learning and communicative aspects of learners' lives across each stage of their multilingual development. In addition, learners view machine translation as a legitimate multimodal tool which they flexibly, critically and pragmatically incorporate within their semiotic repertoires. These findings show how EAL learners are empowered by their own, and their teachers', use of machine translation and offer insights which inform the continued development of translanguaging pedagogies.